Audit Keselamatan Jalan (Studi kasus Jalan HOS Cokroaminoto, Yogyakarta) - M. Ridlwan (Jurusan T.Sipil Fakultas Teknik UMY, 2011)
Audit Keselamatan Jalan (Studi kasus Jalan HOS Cokroaminoto, Yogyakarta)